GE_GERICHTE P/3110/2016 vom 23. August 2018 - GE Cour de justice (2018)
LÉSION CORPORELLE PAR NÉGLIGENCE ; LIEN DE CAUSALITÉ ; DILIGENCE ; APPRÉCIATION DES PREUVES | CP.12.al3; CP.47; CP.125; CPP.107; CPP.139.al2; CPP.389; CPP.433.al1; LCR.26.al1; LCR.36.al3; OCR.14